Text scandals and its social effects among UPV-CM students - Arnaiz, Sheiralou; Mirasol, Rizah Fatima; Salinas, Reynalyn; Salvador, Shiela; Seguiza, Vanessa Khristine
This study, entitled " Text Scandal and its Social Effects among CM, UPV Students," attempted to discover the several forms of text scandal that are being spread out in and outside the UPV-CM campus. In connection with this, the study wanted to analyze the social effects of text scandal in the society. A total of thirty (30) respondents were evenly divided between 15 males and 15 females from the University of the Philippines, College of Mnagement. The questionnaire was used to generate data from the respondents. According from the analysis of data gathered among the respondents, 83% of them are aware of different text scandals passing around even though some of them have not yet received and scandalous text messages. Majority of the respondents are aware of the policies implemented by the government's specialized agency that regulates and monitors the spread of text issues as well as protecting the rights of cell phone owners. Moreover, text scandals greatly affect the values and ethics of the society. Some tend to forget the good manners and proper phone ethics.